EARLY GESTATIONAL LOSS: THE INVISIBILITY OF MOURNING AND THE WOMAN’S EXPERIENCE IN THE PROCESS - Raíssa de Souza, Kellen; Pereira Horta, Tati; Pimenta Faria Galvão, Carolliny; Loreddany Santos Queiroz e Silva, Priscilla; Thereza Martins Pereira Mesquita, Maria; Antunes Aquino Cardoso Gonçalves, Sueli; Gonçalves Silva, Dinariam; Barroso, Roberta; Oliveira de Matos, Cynara; Janaina Carvalho Soares Costa, Naftali; Alves Martins, Jousiane; Scarlatt Durães Oliveira, Pâmela; et al. (Revista Gênero e Interdisciplinaridade, 2026)
Objectives: To understand the experiences and feelings of bereaved women who experienced early gestational loss. Materials and Methods: This is a qualitative study based on social phenomenology. The research was carried out in the city of Montes Claros-MG. The population composed per women who suffered early gestational loss and used the snowball technique. The sample was by theoretical saturation. Individual interviews were carried out conducted by telephone, with the use of a questionnaire of characterize of profile and script with open guiding questions. Results: Were collected 6 interviews lasting approximately 30 minutes were collected. The women interviewed had an average age of 36 years old, most of them married, with a university degree. Thematic categories were listed: Maternal experience in the face of early gestational loss and grief experienced, recognition and appreciation of the bereaved woman by friends, family and health professionals, and the impact of gestational loss on the woman’s life. Most reports deal with regarding the invisibility of gestational loss. Conclusion: It was possible to perceive, through the positive feedback of the participants, the importance of this research, as it represented a form of recognition of gestational loss as a significant event.